Terapi Spiritual Melalui Kaedah Tazkiyah al-Nafs oleh Syeikh Abdul Qadir al-Mandili dalam Kitab Penawar Bagi Hati: Spiritual Therapy Using the Method of Tazkiyah al-Nafs by Syeikh Abdul Qadir al-Mandili Based on Kitab Penawar Bagi Hati - Zaini, Nor Azlinah; Sa’ari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
The concept of soul purification (tazkiyah al-nafs), which is also known as tazkiyah al-qalb is an essential ingredient in the discussion of the Kitab Penawar Bagi Hati compiled by Syeikh Abdul Qadir al-Mandili. He put forward the concepts of soul purification into three main components, which begins with method of controling and preventing the damage of seven human physical, second methods is the treatment and rehabilitation from negative attitudes (mazmumah), whereas the last methods by injection applying positive values (mahmudah). This paper will introduce methods tazkiyah al-nafs that has worked perfectly by Syeikh Abdul Qadir al-Mandili as a solution stemming from soul disease.